Business Valuation Analysis Using the Discounted Cash Flow (DCF) and Price to Earnings Ratio (PER) Methods: Case Study on Telecommunication Subsector Companies Listed on Indonesia Stock Exchange (IDX) - Radius, Radius; Sriwati, Sriwati (Quantitative Economics and Management Studies, 2025)
This study aims to analyze business valuation in telecommunication subsector companies listed on the Indonesia Stock Exchange (IDX) using two valuation methods, namely Discounted Cash Flow (DCF) and Price to Earnings Ratio (PER). The data used in this study were obtained from the company's financial statements and stock market data. The results showed that based on the DCF method, PT Indosat Tbk (ISAT) and PT Smartfren Telecom Tbk (FREN) are overvalued, while PT XL Axiata Tbk (EXCL) and PT Telkom Indonesia (Persero) Tbk (TLKM) are undervalued. Meanwhile, based on the PER method, only ISAT shows an undervalued condition, while other companies are also classified as undervalued compared to the industry average. The differences in results between the two methods shows that the selection of valuation methods affects the interpretation of a company’s stock value.